2009
DOI: 10.1016/j.jinorgbio.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the heme electronic structure and cystathionine β-synthase activity by second coordination sphere ligands: The role of heme ligand switching in redox regulation

Abstract: In humans, cystathionine β-synthase (CBS) is a hemeprotein, which catalyzes a pyridoxal phosphate (PLP)-dependent condensation reaction. Changes in the heme environment are communicated to the active site, which is ~20 Å away. In this study, we have examined the role of H67 and R266, which are in the second coordination sphere of the heme ligands, H65 and C52 respectively, in modulating the heme's electronic properties and in transmitting information between the heme and active sites. While the H67A mutation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 50 publications
5
97
0
1
Order By: Relevance
“…These promising results from E. coli crude extracts encouraged us to attempt to purify the mutants to homogeneity. Several previous attempts to purify CBS mutants resulted in low yields or failed completely due to the unstable mutant conformations, their extreme tendency to aggregation, and heme loss (12,30,31). The presence of chemical chaperones during CBS expression helped to overcome these problems, resulting in homogeneous mutant CBS enzymes as active as WT.…”
Section: Discussionmentioning
confidence: 99%
“…These promising results from E. coli crude extracts encouraged us to attempt to purify the mutants to homogeneity. Several previous attempts to purify CBS mutants resulted in low yields or failed completely due to the unstable mutant conformations, their extreme tendency to aggregation, and heme loss (12,30,31). The presence of chemical chaperones during CBS expression helped to overcome these problems, resulting in homogeneous mutant CBS enzymes as active as WT.…”
Section: Discussionmentioning
confidence: 99%
“…Expression and Purification of hCBS, yCBS, and hCSE-Recombinant full-length hCBS and yeast CBS (yCBS) were purified as described previously (22,23). The expression plasmids encoding hCBS and yCBS were provided by Drs.…”
Section: Methodsmentioning
confidence: 99%
“…The heme iron of human CBS both in the oxidized and reduced state is low spin, hexa-coordinate, being axially bound by the endog-enous ligands His-65 and Cys-52. This heme displays a remarkably low reduction potential (Ϫ350 mV versus standard hydrogen electrode) (13) and acts as a redox-dependent gas sensor because of its ability to react with O 2 and to bind CO and NO ⅐ in the reduced form. Despite the low reduction potential and the fact that most studies on the CBS heme reactivity were carried out in the presence of a large excess of the potent chemical reductant sodium dithionite, it has been recently shown that the diflavin enzyme methionine synthase reductase is able to reduce the CBS heme with NADPH as the electron donor (14,15), conferring greater physiologic relevance to ferrous CBS and its adducts with CO and NO ⅐ .…”
mentioning
confidence: 99%
“…An electrostatic interaction between the Cys-52 thiolate and the guanidinium group of Arg-266 has been identified as a key element in communicating the heme CO binding to the pyridoxal 5Ј-phosphate active site (13,17,18). The reaction with CO proceeds at very low rates showing hyperbolic dependence on CO concentration (14 -16, 19).…”
mentioning
confidence: 99%